Competitividad en el Perú 2019-2020 : una perspectiva de cadena de suministro - Córdova, Miguel (2020)
Nations competitiveness levels define, in some way, their prosperity over time. Peru has demonstrated a progressively recoil between 2017 and 2019 regarding its position in the Global Competitiveness Index (GCI) ranking. Even more, compared with other countries ranked in the GCI and with their Transpacific Alliance partners (Colombia, Chile, and Mexico), it does not show a remarkable growth. This academic note focuses on the discussion about Competitiveness Report 2019 and 2020 for Peru, under a supply chains perspective, since this is a natural and relevant facilitator for country’s competitiveness. Therefore, it develops the infrastructure and logistics pillars included in these reports, and at the end it presents conclusions and recommendations from the discussion made.